An Experimental Test of Design Alternatives for the British 3G / UMTS Auction - Klaus Abbink; Bernd Irlenbusch; Paul Pezanis-Christou; Bettina Rockenbach; Abdolkarim Sadrieh; Reinhard Selten (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
In spring 2000, the British government auctioned off licences for Third Generation mobile telecommunications services. In the preparation of the auction, two designs involving each a hybrid of an English and a sealed-bid auction were suggested by the government: a discriminatory and a uniform price variant. We report an experiment on these two designs, and also compare the results to those with a pure English auction. Both hybrids are similar in efficiency, revenue differences disappear as bidders get experienced. Compared to the discriminatory format, the pure English auction gives new entrants better chances.
Keywords: C90; D44; 330; Spectrum auctions; UMTS; experiments